The structure of (C-60)(N) clusters - Doye, J; Wales, D (1996)
We present likely candidates for the lowest energy minima of (C60)N clusters with N ≤ 80 modelled by the Girifalco potential. For N > 13 the clusters exhibit decahedral and close-packed structures, rather than icosahedral. This is a consequence of the short range of attraction of the C60 intermolecular potential relative to the equilibrium pair separation.